From Game to Grammar: Analysing the ESP Needs of E-sport - Anwar, Aslam Nurdin; Suharyanto, S (Universitas Muhammadiyah Surakarta, 2024)
Purpose: This research investigates the specific language needs of esports professionals in Indonesia, particularly assessing whether conventional English classes effectively support their international success. It also explores language barriers that hinder team dynamics and performance. As the global esports industry continues to expand, effective communication among players is increasingly recognized as a critical factor in achieving team success. Methodology: This study employed a mixed-methods approach, combining both quantitative and qualitative data. The participants consisted of 17 esports professionals, including players, coaches, managers, casters, streamers, and brand ambassadors. Data were gathered through structured questionnaires, in-depth interviews, and direct observations during esports events organized by local esports bodies. Results: The findings indicate that conventional English classes do not meet the specialized communication needs of esports professionals. Participants reported difficulties in understanding contractual agreements, following instructions from international coaches, and communicating effectively during international matches. These communication gaps negatively impact team cohesion and performance. Applications/Originality/Value: The study underscores the urgent need for English for Specific Purposes (ESP) programs tailored to the esports context. The results are valuable for educators, policymakers, and esports organizations in designing targeted language training initiatives that align with the unique demands of the esports industry and enhance the global competitiveness of Indonesian esports professionals.